Hubungan Pengetahuan Ibu Hamil terhadap Kepatuhan Pemeriksaan Antenatal Care - Rasmin hi Abd Muthalib; Supriyanti R Usman (Jurnal Sehat Mandiri, 2024)
The Ternate City Health Service reported a total of 1,890 cases of child deaths in 2022, with a significant increase in cases of anemia, hypertension and breech. The aim of the research is to determine the relationship between knowledge of pregnant women and compliance with antenatal care (ANC) examinations at the Kalumata Community Health Center, Ternate City in 2023. This research method is analytical and quantitative. The research design used was cross sectional (cross-sectional). The total sample was 20 respondents carried out in the Kalumata Community Health Center Work Area. The sample collection technique uses total sampling, where the entire population is used as a sample. Data analysis used Univariate and Bivariate analysis, using the Chi-Square test to see whether there was a relationship between the independent variable and the dependent variable. Materials for interviews using questionnaire instruments. There is a significant relationship between knowledge of pregnant women and compliance with ANC implementation with a value of p = 0.002. Of the 20 samples, 9 people had good knowledge, 5 people had moderate knowledge, and 6 people had poor knowledge. Conclusion: The results of the study show that there is a significant relationship between knowledge and the fulfillment of ANC. Pregnant women who have a higher level of knowledge tend to be more compliant with ANC practices. The advice that can be given is to increase the knowledge of pregnant women through effective education regarding the benefits and importance of ANC.